Sistem Informasi Pemasaran Perumahan Dan Pembayaran Konsumen Pada Pt.Duta Dharmasraya Pratama Berbasis Web - Mahfuddin Hanif Rizki; Firdaus (Universitas Putra Indonesia YPTK Padang, 2023)
Abstract In the current era of globalization, the development of science and technology continues to advance rapidly. This encourages various changes that are very fast in terms of life and it is undeniable that these changes are felt in everyday life. One of the results of utilizing technological advances is the use of computers, and one of the main supporting factors is because computer users are more effective in the current era of globalization and because of that in this day and age it feels very minimal if a company cannot rely on existing technology. In this current era, therefore, every company must be able to develop and even use technology optimal, PT. Duta Dharmasrya Pratama PT has been established since 2018 and is engaged in the property sector, namely as a housing developer (Developer). This company is currently marketing housing in the Dharmasrya district, which is located in the province of West Sumatra.